2021
DOI: 10.3390/agronomy11061105
|View full text |Cite
|
Sign up to set email alerts
|

The Nutritional Value and Safety of Genetically Unmodified Soybeans and Soybean Feed Products in the Nutrition of Farm Animals

Abstract: Post-extraction soybean (Glycine max (L.) Merr.) meal is widely used as a basic protein feed for farm animals, especially poultry and pigs. Products made from unmodified soybean seeds are an alternative to imported GMO soybean meal. The aim of the study was to develop feed products from popular European varieties of genetically unmodified soybeans, which can be produced on small and medium-sized farms, and to assess their nutritional value and safety to livestock. The research was conducted on the seeds of thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
3
5
0
Order By: Relevance
“…The amount of trypsin inhibitors determined in soybean meal and in extruded full-fat soybean in our own studies corroborated the results of Milczarek et al [6]. Similarly, Świ ątkiewicz et al [38], analysing the content of trypsin inhibitors in soybean products, found 9-11 mg•g −1 in extruded full-fat soybean, 6-8 mg•g −1 in soybean press cake and 2.8 mg•g −1 in standard GM soybean meal. Compared to our own results, Wu et al [11] determined more trypsin inhibitors in soybean meal.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The amount of trypsin inhibitors determined in soybean meal and in extruded full-fat soybean in our own studies corroborated the results of Milczarek et al [6]. Similarly, Świ ątkiewicz et al [38], analysing the content of trypsin inhibitors in soybean products, found 9-11 mg•g −1 in extruded full-fat soybean, 6-8 mg•g −1 in soybean press cake and 2.8 mg•g −1 in standard GM soybean meal. Compared to our own results, Wu et al [11] determined more trypsin inhibitors in soybean meal.…”
Section: Discussionsupporting
confidence: 91%
“…The level of crude fat in soybean meal and in extruded full-fat soybean was close to that determined by Milczarek et al [6]. Świ ątkiewicz et al [38] showed a similar amount (216 g•kg −1 ) of fat in extruded fullfat soybean but a higher amount (88 g•kg −1 ) in soybean expeller cake. According to Niwi ńska et al [39], the protein product derived from full-fat non-GM soybean seeds subject to pressure-thermal processing contains a lot of protein and fat as the source of energy and a low amount of anti-nutrients.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…There were no statistically significant differences in the amount of crude fibre available in S. frugiperda (S2) and S. frugiperda (S3) (Figure 1). A comparison of the crude fibre of FAW larvae, BSF larvae, HF larvae and Soya bean indicated that the amount of crude fibre was the Source: Data from current study, Kwikiriza, et al, 2016;Khan, et al, 2018;Sayed et al, 2019 andŚwiątkiewicz et al, 2021 Kwikiriza, et al, 2016;Khan, et al, 2018;Sayed et al, 2019 andŚwiątkiewicz et al, 2021 same (Tables 2 to 4). Crude fibre of < 10% for S. frugiperda in the current study is in line with the report of Williams et al (2016), which is an indication that their bodies were not hardened.…”
Section: Discussionmentioning
confidence: 80%